Employee engagement and turnover intention among Islamic Bankers in Brunei Darussala - Salahudin, Shahrul Nizam; Ramli, Hani Suhaila; Alwi, Mohd Nur Ruzainy; Abdullah, Muhammad Safizal; Abdul Rani, Nasir (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Employee engagement and turnover intention are two factors that are important predictors of organisational success and failure. These are key indicators of issues that are related to the organisations’ workforce. This study explores the levels of engagement and turnover intention between the different demographics of the Islamic bank employee in Brunei Darussalam. The study also examined the effects of employee engagement on the turnover intention among the employees. A total of 119 bankers completed the survey. Survey items were adapted from previous literature and subjected to Content Validity Index by 12 experienced Human Resource Managers. Except for income levels, the findings indicate no significant differences in terms of employee engagement and turnover intentions between the different demographics of the bankers. Also, Employee engagement was found to significantly impact turnover intentions among the respondents. The mixed results obtained from this study signal a need to further study engagement and turnover intention among employees in the banking sector especially in Brunei Darussalam.